Pengaruh Beberapa Sistem Pembibitan terhadap Pertumbuhan Kelapa Dalam (Cocos nucifera) di Pembibitan - Manambangtua, Alfred Pahala; Hidayat, Tony Surya (Seminar Nasional Lahan Suboptimal, 2024)
Manambangtua, A. P., & Hidaya, T. S. (2024). The effect of some breeding systems on the growth of tall coconut (Cocos nucifera) in the nursery. In: Herlinda S et al.(Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 383–388).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Coconut is a plant often used by people as a source of life. Coconut is an important contributor to food security at the agricultural level and has high added value at the industrial level. The health of the plants influences the growth and high production of coconut plants in the field during the nursery period. Farmers know three systems or techniques for breeding systems. Each breeding system has advantages and disadvantages, but it is unknown which produces the best plant growth in the main nursery. This research aimed to determine the breeding system that makes the best coconut plant growth in the nursery. The research at the Mapanget Temptation Garden, Palm Plant Research Institute, was conducted for 7 months, from July 2021 to January 2022. The research was conducted using a completely randomized design with 3 treatments and 3 replications. So that 9 experimental units were obtained, and each experimental unit consisted of 8 plants, so 72 plants were needed. breeding using polybags, in land with close planting distance, and in land with sparse planting distance (spaced). The variables observed were plant height and stem diameter. Based on the research results on plant height parameters, significantly different results were obtained. It can be seen that the nursery system rarely shows higher values compared to other treatments 2 to 6 months after treatment (mat). In contrast, the stem diameter parameter shows results that are not significantly different in all treatments.